Dysgenesis and Dysfunction of the Pancreas and Pituitary Due to FOXA2 Gene Defects - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (ENDOCRINE SOC, 2021)
Context: Developmental disorders of the pituitary gland leading to congenital hypopituitarism can either be isolated or associated with extrapituitary abnormalities (syndromic hypopituitarism). A large number of syndromic hypopituitarism cases are linked to mutations in transcription factors. The forkhead box A2 (FOXA2) is a transcription factor that plays a key role in the central nervous system, foregut, and pancreatic development. Objective: This work aims to characterize 2 patients with syndromic hypopituitarism due to FOXA2 gene defects. Results: We report a novel heterozygous nonsense c.616C>T(p.Q206X) variant that leads to a truncated protein that lacks part of the DNA-binding domain of FOXA2, resulting in impaired transcriptional activation of the glucose transporter type 2 (GLUT2)-luciferase reporter. The patient is the sixth patient described in the literature with a FOXA2 mutation, and the first patient exhibiting pancreatic hypoplasia. We also report a second patient with a novel de novo 8.53 Mb deletion of 20p11.2 that encompasses FOXA2, who developed diabetes mellitus that responded to sulfonylurea treatment. Conclusion: Our 2 cases broaden the molecular and clinical spectrum of FOXA2-related disease, reporting the first nonsense mutation and the first case of pancreatic dysgenesis.
Keywords: FOXA2; congenital hypopituitarism; diabetes; hyperinsulinism; pancreatic hypoplasia; abdominal heterotaxy; DEVELOPMENTAL DELAY; SONIC HEDGEHOG; MUTATION; DELETION; PANHYPOPITUITARISM; HYPOPITUITARISM; 20P; HYPERINSULINISM; HNF-3-BETA; PATHWAYS